Embedding School Health into School Improvement Policy - Howard S Adelman; Linda Taylor (Shiraz University of Medical Sciences, 2014)
Context: No one seriously argues against the common sense notion that physical and mental health problems can profoundly affect learning and performance. The reality, however, is that health concerns are only one set of factors that interfere with success at school, and when a focus on health is advocated as a separate agenda, the efforts tend to be marginalized in school improvement policy and practice. Evidence Acquisition: This paper is the product of decades of research conducted by our center at UCLA. It reflects policy and practice analyses, prototypes developed for policy, practice, infrastructure, and systemic change, and direct implementation efforts with schools, districts, and state departments of education. Results: We find that school health concerns currently are marginalized in school improvement policy. As a result, prevailing approaches to physical and mental health in schools are too limited in nature and scope and are implemented in a piecemeal and fragmented manner. Improving the situation requires embedding such concerns into a framework that addresses the fuller range of factors that can interfere with learning and teaching. To this end, we emphasize moving in new directions to transform how schools can comprehensively address such factors. Conclusions: It is time to do more than advocate for expanding the range of health programs and services. Needed is a fundamental transformation of student and learning supports so that all the fragmented pieces are unified as a primary and essential component that is fully integrated into school improvement policy and practice for every school.